Pengrauh Edukasi Menggunakan Media Leaflet dan Website terhadap Pengtahuan Mahasiswa Mengenai Faktor Risiko Diabetes Mellitus - Santika Citra Dewi; Ratih Kurniasari (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2022)
Efforts to manage diabetes mellitus do not only focus on the management and control of the disease, but must also focus on efforts to prevent it. One way to control diabetes can be done by providing education about risk factors for diabetes mellitus. There are various types of media that can be used in health education to maximize message delivery, which can be in the form of print media (leaflets) or media that use the internet (websites). The purpose of this study was to determine the effect of providing education using leaflets and websites to increase student knowledge about risk factors for diabetes mellitus. This study is a quasi-experimental study with a pre-test post-test group design. The results of this study indicate that educational media leaflets and websites can both increase students' knowledge about risk factors for diabetes mellitus.